Application of Recreational Resources of Liudvinavas to Meet Social and Cultural Needs of the Community (Laisvalaikio tyrimai, 2018)
Research background. Recreation as a phenomenon is gaining more and more attention from the government, scientists and other researchers. It is becoming more and more important to preserve population’s dynamic activity, energy and health because of a faster pace of life and increased workload. Any chosen form of recreation allows a person to get some rest, regain peace, relax from tension and worries, and experience new things, etc. This article examines the theoretical point of view of recreation and the need for it. The purpose of the conducted study was to determine the application of recreational resources of Liudvinavas to satisfy the needs of its residents. The problem of the research. Only little research has been conducted in rural areas, including Liudvinavas recreational environmental studies, its application for recreation. The purpose of the research. To analyse the application of recreational resources of Liudvinavas to satisfy the social and cultural needs of the community. Methods of the research. Quantitative and qualitative. Results and conclusions. Recreational potential in Liudvinavas is quite big but it requires detailed research to be done. Recreational potential in leisure, forests, cognitive and sports (active) recreation can be used without requiring big investments. Employing a recreational specialist in Liudvinavas who would be in charge of organising leisure (recreation) activities would help to meet the needs of local residents as well as those visiting the town. In the future it can be used to promote entrepreneurship. Usually a passive and local form of recreation is chosen, but the potential of Liudvinavas nature is great for the active forms of recreation as well. Respondents usually prefer recreational resources of nature such as forests, water and coastlines, natural heritage objects that are suitable for people’s leisure and entertainment. Therefore it is important to adapt all those resources of nature to be suitable to satisfy the recreational needs. Both younger and older residents of Liudvinavas would like to have more organised gatherings and activities, more recreation of sports and wellness, and the majority would prefer a lake shore that is nicely arranged and adapted for leisure.Keywords: recreation, globalization, recreational resources, natural resources.